The Development of Competences Specific to Primary Education Objects as a Prerequisite for the Development of Students' Digital Competence - Marius Bănuț; Ion Albulescu (Babes-Bolyai University, 2023)
The development of the digital competence is a lifelong learning goal, which will remain stable, taking into account the digitization of societies and global economies. In this context and unlike the other European states, in the Romanian curriculum, the digital competence can not be found among the acquisitions of learning at the primary education level. In the absence of some clearly formulated learning objectives, which could be integrated into the development of digital competence, the teaching staff has the option to adapt the learning activities or to propose some new ones, so that the projection of the lessons ensures a teaching approach adequate to the acquisition of digital knowledge and skills. This paper highlights the possibilities of developing the specific competences of the objects in the current education framework plan for primary education, in a prototype approach to support the premise of their integration in the development of digital competence.